(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
The availability of shelters in a specific density is expected to increase the production of mud crabs (Scylla serrata) in a recirculation system. Shelter, as one of the abiotic factors, plays a pivotal role in reducing death caused by cannibalism of crab and suppressing the stress levels of biota. Recirculation Aquaculture System (RAS), with the culture box capacity 60 L supported by the shelters, is predicted to produce the best physiological and growth responses of mud crabs. This present study aims to evaluate the effect of shelter addition in the environmental recirculation system on the physiological responses and production of mud crabs S. serrata with a density of 10 crabs per one culture box containing 60 L of seawater. The research was set up with three treatments of shelter addition, i.e., two shelters (S2), four shelters (S4), six shelters (S6), and control without shelter (C). Results showed that S6 was the best treatment with a survival rate of 73.33 ± 5.8%, a specific growth rate of 0.886 ± 0.014%, the growth rate of carapace width 0.024 ± 0.004 cm/day, and the lowest feed conversion ratio than those of other treatments. S6 treatment significantly influenced the total hemocyte count of crabs at the early cultivation (P <0.05). Addition of six shelters could optimize the growth of mud crabs with a stocking density of 10 crabs in one culture box.